Synthesis and Anti-Cancer Activity In Vitro of Synephrine Derivatives - Ekaterina M. Zhidkova; Evgeniya S. Oleynik; Ekaterina A. Mikhina; Daria V. Stepanycheva; Diana D. Grigoreva; Lyubov E. Grebenkina; Kirill V. Gordeev; Ekaterina D. Savina; Andrey V. Matveev; Marianna G. Yakubovskaya; Ekaterina A. Lesovaya (Biomolecules)
Glucocorticoids (GCs) are routinely used to treat hematological malignancies; however, long-term treatment with GCs can lead to atrophic and metabolic adverse effects. Selective glucocorticoid receptor agonists (SEGRAs) with reduced side effects may act as a superior alternative to GCs. More than 30 SEGRAs have been described so far, yet none of them reached clinical trials for anti-cancer treatment. In the present work, we propose a novel approach to increase the number of potential SEGRAs by obtaining derivatives of synephrine, a molecule of natural origin. We synthesized 26 novel compounds from the class of synephrine derivatives and characterized them by HRMS, and 1H and 13C NMR. We evaluated in vitro anti-cancer effects in leukemia K562 and lymphoma Granta cells using the MTT assay and studied their potential affinity for the glucocorticoid receptor (GR) in silico using the molecular docking approach. The novel derivative 1-[4-(benzyloxy)phenyl]-2-(hexylamino)ethanol (10S-E2) with the highest GR affinity in silico exhibited cytotoxic activity against K562 and Granta cells after 24 h of treatment at the concentration of approximately 13 µM which correlated with its highest MolDock Score. The other compound with high GR affinity, 2-(hexylamino)-1-(4-nitrophenyl)ethanol (13S-G2), demonstrated cytotoxicity in both cell lines at concentrations of 50–70 µM. Overall, our results may provide a solid rationale for developing and further investigating synephrine derivatives as SEGRAs with anti-cancer activity.